Stimulating Organizational Citizenship Behavior (OCB) research for theory development: Exploration of leadership paradigms - Bambale, Abdu Ja’afaru; Mohd Shamsudin, Faridahwati; Subramaniam, Chandrakantan (Human Resource Management Academic Research Society (HRMARS), 2011)
This paper synthesizes major leadership paradigms for the purpose of identifying possible ways of influencing Organizational Citizenship Behaviors (OCBs) to improve the functioning of organizations.The leadership paradigms were extended to old and modern categories to provide for systematic understanding of their antecedents and potential influence patterns.The leadership approaches reported to have positive relationships with organizational citizenship behaviors include transformational leadership, charismatic leadership, and ethical leadership paradigms.We have found many modern leadership paradigms not to have been empirically investigated for possible relationships with OCB.This paper therefore discusses the dynamics and potentials for researches within the realms of the leadership paradigms and the OCB field.